Representasi Alam Pada Film Mansoer Karya Rashed Al Harmoodi: Kajian Ekolinguistik - Andi Muh Fathurrahman Lahaji; Abdul Basid; Ma'rifatul Munjiah (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2025)
The purpose of this study is to reveal the representation of nature in Rashed Al-Harmoodi's Mansour movie in the study of Ecolinguistics. This research includes qualitative research. The data collection techniques used are listening and note-taking techniques. The data analysis technique in this study uses the critical Ecolinguistic analysis model developed by Arran Stibbe. The results of this study indicate that the representation of nature in the film Mansour by Rasheed Al-Harmoodi consists of the form representation of nature in this film divided into 2 aspects. The main aspect: (a) there are 14 Arabic words, transliteration, ecological meaning in the form of nature representation, and the second aspect is the description of Nature in the form of desert landscapes and the beauty of oases. The second aspect (b) there are descriptions of Nature in the form of desert landscapes and the beauty of oases, More specifically, some of the main elements in the description of the desert include the vast expanse of sand, the scorching sun and the vast sky, the beauty of the desert at night, and the beauty of the oasis has a green miracle in the middle of the desert, a place of rest and tranquility, a beautiful view at dusk.